Screening Performance Characteristics of Ultrasonography in Confirmation of Endotracheal Intubation; A Systematic Review and Meta-analysis - Farrokhi, Mehrdad; Yarmohammadi, Bardia; Mangouri, Amir; Hekmatnia, Yasaman; Bahramvand, Yaser; Kiani, Moein; Nasrollahi, Elham; Nazari-Sabet, Milad; Manoochehri-Arash, Niusha; Khurshid, Maria; Mosalanejad, Shima; Hajizadeh, Vida; et al. (Archives of Academic Emergency Medicine, 2021)
Introduction: Recent studies have suggested that point-of-care ultrasonography can be used for confirming the placement of endotracheal tube. This systematic review and meta-analysis aimed to investigate the sensitivity and specificity of ultrasonography for confirming endotracheal tube placement. Methods: In this meta-analysis, systematic search of the previous published papers investigating the diagnostic accuracy of ultrasonography for confirmation of endotracheal tube placement was performed. Seven electronic databases, including PubMed, Scopus, Google Scholar, EBSCO, EMBASE, Web of Science, and Cochrane Database were searched up to July 2021, for all relevant articles published in English on this topic. Meta-DiSc version 1.4 software was used for statistical analysis. Results: The estimated pooled sensitivity and specificity of ultrasonography for confirmation of endotracheal tube location were 0.98 (95% CI: 0.98–0.99) and 0.94 (95% CI 0.91–0.96), respectively. The pooled positive likelihood ratio and negative likelihood ratio were 5.94 (95% CI 4.41–7.98) and 0.03 (95% CI: 0.02-0.04), respectively. The diagnostic odds ratio of ultrasonography was 281.47 and the area under hierarchical summary receiver operating characteristic (HSROC) revealed an appropriate accuracy of 0.98. Conclusion: Ultrasonography has high diagnostic accuracy and can be used as a promising tool for confirmation of endotracheal tube placement, especially in critically ill patients or when capnography is not available, or its result is equivocal.